2020
DOI: 10.1016/j.hrthm.2019.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of extensive diagnostic workup in young athletes and nonathletes with complex ventricular arrhythmias

Abstract: Total word count: 4862 24 This research did not receive any specific grant from funding agencies in the public, commercial, 25 or non-profit sectors. 26 2 The authors have no conflicts to disclose. Abstract 41 Background. Ventricular tachyarrhythmias (VA) represent the first cause of death in athletes. The 42 difference between electroanatomic substrate in athletes and non-athletes with complex VA is 43 unknown. 44 45 Objective. To compare the electroanatomic substrate of complex VA in athletes versus non-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In particular, these authors considered that a vigorous exercise and the related haemodynamic loading changes, through an increased oxygen demand and increased release of catecholamines/changes in free fatty acid metabolism, may lead to acute effects (right heart dilation, diastolic dysfunction), sub‐acute effects (overexpression of cardiac fibrotic markers, collagens,fibronectin‐1), and finally chronic effects (determining patchy areas of fibrosis, an ideal substrate for VA) 13,14 . Although many studies confirmed exercise‐induced RV fibrosis 21‐23 it is still debated to what extent the controversial “exercise‐induced" ARVC and the “Philippides cardiomyopathy” associated with potential pathological or physiological findings. A RV dilatation and hypokinesia were noted in at least one‐third of endurance athletes, compared with a potential LV impairment 24‐26 .…”
Section: The Athlete's Right Heart Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, these authors considered that a vigorous exercise and the related haemodynamic loading changes, through an increased oxygen demand and increased release of catecholamines/changes in free fatty acid metabolism, may lead to acute effects (right heart dilation, diastolic dysfunction), sub‐acute effects (overexpression of cardiac fibrotic markers, collagens,fibronectin‐1), and finally chronic effects (determining patchy areas of fibrosis, an ideal substrate for VA) 13,14 . Although many studies confirmed exercise‐induced RV fibrosis 21‐23 it is still debated to what extent the controversial “exercise‐induced" ARVC and the “Philippides cardiomyopathy” associated with potential pathological or physiological findings. A RV dilatation and hypokinesia were noted in at least one‐third of endurance athletes, compared with a potential LV impairment 24‐26 .…”
Section: The Athlete's Right Heart Remodelingmentioning
confidence: 99%
“…The authors concluded that chronic RV damage in endurance master athletes is unlikely, since the RV ejection fraction did not differ between the two groups, and no correlations were found for the LV/RV volumes and the ejection fraction with natriuretic peptide. 29 However, although it is clear that endurance sport may promote RV changes "compatible" with a diagnosis of ARVC, [21][22][23][24][25][26][27][28] the hypothesis of a definite "exercise-induced" cardiomyopathy is still questionable. Cardiac fibrosis and remodeling, although initially reversible, could eventually become permanent due to repeated myocardial injury.…”
Section: The Athlete's Right Heart Remodelingmentioning
confidence: 99%
“…18 Besides necropsy, EMB studies performed in the 1980s and 1990s, provided major insights on possible myocardial disorders that may cause life-threatening VA with an apparently normal heart. [19][20][21][22][23][24][25][26][27][28][29][30][31] Clinical setting and major findings and peculiar features of these studies are summarized in Table 1. Although in most of these studies EMB processing was limited to histology, thus neither including immunohistochemistry nor molecular biology, pathological findings were reported in most patients, even those with a milder arrhythmic burden.…”
Section: Pathological Substrates Of Va and Scd With Apparently Normalmentioning
confidence: 99%
“…In the last decades several studies have documented that EMB represents an important tool not only in clinical practice but also for its application as a research tool in the fields of cardiomyopathy and arrhythmias [19][20][21][22][23][24][25][26][27][28][29][30][31] (Table 1).…”
Section: The Diagnostic Contribution Of Emb In Patients With Apparentmentioning
confidence: 99%
See 1 more Smart Citation